REKONSTRUKSI PERAN GURU PENDIDIKAN ISLAM DI ERA POSTTRUTH - Sukarman . (Universitas Wahid Hasyim Semarang, 2019)
AbstractThis study describes the need to reconstruct the role of Islamic educationteachers in the post-truth era. This research is a descriptive study using aqualitative approach. In the era of post-truth, hoax, bullshit and radical ideological propaganda a threat in life. So the role of the teacher needs to be reconstructedbecause of the conditions and demands of the times. Society in the post-truth eracannot be separated from the digital world. Likewise, students as the millennialgeneration who live in the digital era need to get attention and bang from theteacher. In the post-truth era teachers are not only enough to have basicqualifications and competencies as educators. So that in this study the teacherbesides having competence as an ideal educator, teachers need to be literate intechnology and media literacy, spirit of nationalism, become educators and jihadisin the real world and cyberspace. In other words the role of Islamic educationteachers in the post-truth era is not only to be educators and jihadis in the realworld but also in cyberspace.Keywords: teacher, Islamic education, post-truthAbstrakPenelitian ini memaparkan tentang perlunya merekonstruksi peran gurupendidikan Islam di era post-truth. Penelitian ini merupakan penelitian deskriptifdengan menggunakan pendekatan kualitatif. Di era post-truth, hoax, bullshit danpropaganda ideologi yang radikal memenjadi ancaman dalam kehidupan. Sehinggaperan guru perlu direkonstruksi karena kondisi dan tuntutan zaman. Masyarakat diera post-truth tidak dapat lepas dari dunia digital. Demikian juga peserta didiksebagai generasi mileneal yang hidup di era digital perlu mendapat perhatian dandentuhan dari guru. Di era post-truth guru tidak hanya cukup dengan memilikikualifikasi dan kompetensi dasar sebagai pendidik. Sehingga dalam penelitian iniguru selain memiliki kompetensi sebagai pendidik yang ideal, guru perlu melekteknologi dan melek media, berjiwa nasionalisme, menjadi pendidik dan jihadis didunia nyata dan dunia maya. Dengan kata lain peran guru pendidikan Islam di erapost-truth adalah tidak hanya menjadi pendidik dan jihadis didunia nyata tetapi juga di dunia maya.Kata kunci : guru, pendidikan Islam, post-truth